2021
DOI: 10.1186/s12885-021-08084-0
|View full text |Cite|
|
Sign up to set email alerts
|

“Randomized trial of physical activity on quality of life and lung cancer biomarkers in patients with advanced stage lung cancer: a pilot study”

Abstract: Background Lung cancer survivors need more options to improve quality of life (QoL). It is unclear to what extent patients with advanced stage disease are willing to participate in home-based physical activity (PA) and if these interventions improve QoL. The goal of our study was to determine interest in participating in our 3-month home-based walking regimen in patients with advanced stage lung cancer. We used a randomized design to evaluate for potential benefit in PA and patient-reported out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
68
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(68 citation statements)
references
References 54 publications
0
68
0
Order By: Relevance
“…After reading the full texts, 21 studies were included in the final analysis. 18 , 19 , 21 , 23 40 See Figure 1 for the flowchart of the detailed screening process.…”
Section: Resultsmentioning
confidence: 99%
“…After reading the full texts, 21 studies were included in the final analysis. 18 , 19 , 21 , 23 40 See Figure 1 for the flowchart of the detailed screening process.…”
Section: Resultsmentioning
confidence: 99%
“…National policies should further focus on reducing cancer incidence and preventing disability. For example, lifestyle interventions, including diet and physical activity when combined with chemotherapy can enhance treatment efficacy [21,22], or different types of counseling, psychoeducation or therapy can help with cancer-related fatigue [23].…”
Section: Discussionmentioning
confidence: 99%
“…The review also indicates a significant bias in terms of the sample and respondents (see Appendix 1, Figure 4). Prior studies seemed to have majorly focused on females [36,78,98,114] and respondents of Caucasian ethnicity [21,84,91]. Few studies have studied the effects of mHealth interventions on vulnerable sections of the population, such as immigrants [79], or ethnic groups such as Koreans [114] or Chinese Americans [107].…”
Section: Theme 3: Methodological Approachmentioning
confidence: 99%
“…Moreover, prior research has suggested a degree of fragmentation in prior research designs and methodologies. For example, some studies have focused on understanding cancer management in specific demographic profile cohorts, such as elderly or older [35][36][37] or adolescent [34,38,39] populations, while others have focused on elucidating mHealth interventions for patients afflicted with a specific form of cancer, such as colorectal cancer [40] or breast cancer [41]. This widespread fragmentation indicates the need to amalgamate the prior research to identify the limitations in the present knowledge, incumbent gaps, and scope for future research through the use of systematic literature reviews (SLRs).…”
Section: Introductionmentioning
confidence: 99%